Synthetic Biology and Metabolic Engineering Employing Escherichia coli for C2–C6 Bioalcohol Production - Liang, Liya; Liu, Rongming; Freed, Emily F.; Eckert, Carrie A. (Frontiers in Bioengineering and Biotechnology, 2020)
Biofuel production from renewable and sustainable resources is playing an increasingly important role within the fuel industry. Among biofuels, bioethanol has been most widely used as an additive for gasoline. Higher alcohols can be blended at a higher volume compared to ethanol and generate lower greenhouse gas (GHG) emissions without a need to change current fuel infrastructures. Thus, these fuels have the potential to replace fossil fuels in support of more environmentally friendly processes. This review summarizes the efforts to enhance bioalcohol production in engineered Escherichia coli over the last 5 years and analyzes the current challenges for increasing productivities for industrial applications.